Post 2010 evaluation of Zimbabwe as a preferred tourist destination. - Zhou Zibanai (AFRICAJOURNALS, 2023)
This study is a post 2010 evaluation of Zimbabwe as a preferred tourism destination. The post 2010 timeline was deliberately chosen since it was believed to be a water-shed period or game changer in Zimbabwe`s tourism landscape following the successful hosting of the Fifa 2010 world cup by South Africa which is Zimbabwe`s major economic trading partner. The hosting of the prestigious soccer extravaganza by South Africa was speculated to reconfigure the architecture of Zimbabwe`s tourism sector that had been in a comatose for close to a decade. The study established that the post 2010 period is a landmark as it marked the somewhat thawing of political and economic relations between Zimbabwe and western countries following the consummation of the inclusive government that stabilised the economy. The tourism sector was speculated to have been given a new lease of life riding on the perceived spin-offs from South Africa, warming of the international community to Zimbabwe, and the dollarization of the economy. A dozen variables were used as anchor elements against which Zimbabwe was evaluated. A questionnaire survey was used on 80 hotels, 60 tour operators, 20 key informants, and 50 international tourists at Great Zimbabwe and Victoria Falls. Results confirm that Zimbabwe indeed has raised the bar higher as a preferred tourist destination relative to other southern Africa countries as attested to by playing host to the UNWTO`s General Assembly and ATA congress, and also being the recipient of the tourism award from the European Tourism Council. On the flip-side, visa and pricing regimes are still frowned upon; however, there is huge potential for the country to do better.